Poverty/Poor - Breuer, Saskia Rebecca (Encyclopedia of the Bible and its Reception)

Vom Benutzen der Historie für Ideologeme der Gegenwart. Anmerkungen zu Schlesingers Überlegungen zum „Kampf der Schulen“ - Vukadinovic, Vojin Sasa (Die Wir-gegen-die-Gesellschaft. Warum der von Arthur M. Schlesinger vor 30 Jahren diagnostizierte Samen der identitätspolitischen Spaltung aufgegangen ist)

Siebter Oktober Dreiundzwanzig. Einleitung - Vukadinovic, Vojin Sasa (Siebter Oktober Dreiundzwanzig)

Editorial - Bartels, Mette; Vukadinovic, Vojin Sasa (Ariadne. Forum für Frauen- und Geschlechtergeschichte)

Editorial. Siebter Oktober Dreiundzwanzig - Barberi, Alessandro; Serloth, Barbara; Vukadinovic, Vojin Sasa (ZUKUNFT. Die Diskussionszeitschrift für Politik, Gesellschaft und Kultur)

Siebter Oktober Dreiundzwanzig (ZUKUNFT. Die Diskussionszeitschrift für Politik, Gesellschaft und Kultur)

Antisemitismus (Medienimpulse. Beiträge zur Medienpädagogik)

Mathematical Structures - Hilgert, Joachim

Vorwort zur zweiten Auflage - Vukadinovic, Vojin Sasa (Freiheit ist keine Metapher. Antisemitismus, Migration, Rassismus, Religionskritik)

Machine learning predicts peak oxygen uptake and peak power output for customizing cardiopulmonary exercise testing using non-exercise features - Wenzel, Charlotte; Liebig, Thomas; Swoboda, Adrian; Smolareck, Rika; Schlagheck, Marit Lea; Walzik, David; Groll, Andreas; Goulding, Richie P.; Zimmer, Philipp (European Journal of Applied Physiology)
Abstract Purpose Cardiopulmonary exercise testing (CPET) is considered the gold standard for assessing cardiorespiratory fitness. To ensure consistent performance of each test, it is necessary to adapt the power increase of the test protocol to the physical characteristics of each individual. This study aimed to use machine learning models to determine individualized ramp protocols based on non-exercise features. We hypothesized that machine learning models will predict peak oxygen uptake ( $$\dot{V}$$ V ˙ O 2peak ) and peak power output (PPO) more accurately than conventional multiple linear regression (MLR). Methods The cross-sectional study was conducted with 274 (♀168, ♂106) participants who performed CPET on a cycle ergometer. Machine learning models and multiple linear regression were used to predict $$\dot{V}$$ V ˙ O 2peak and PPO using non-exercise features. The accuracy of the models was compared using criteria such as root mean square error (RMSE). Shapley additive explanation (SHAP) was applied to determine the feature importance. Results The most accurate machine learning model was the random forest (RMSE: 6.52 ml/kg/min [95% CI 5.21–8.17]) for $$\dot{V}$$ V ˙ O 2peak prediction and the gradient boosting regression (RMSE: 43watts [95% CI 35–52]) for PPO prediction. Compared to the MLR, the machine learning models reduced the RMSE by up to 28% and 22% for prediction of $$\dot{V}$$ V ˙ O 2peak and PPO, respectively. Furthermore, SHAP ranked body composition data such as skeletal muscle mass and extracellular water as the most impactful features. Conclusion Machine learning models predict $$\dot{V}$$ V ˙ O 2peak and PPO more accurately than MLR and can be used to individualize CPET protocols. Features that provide information about the participant's body composition contribute most to the improvement of these predictions. Trial registration number DRKS00031401 (6 March 2023, retrospectively registered).

Optimising Heat Planning: Cost effective heat planning for low carbon district heating - Divkovic, Denis; Kirschbaum, Julia; Rahlf, Henning Christoph; Knorr, Lukas; Meschede, Henning

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - Javelle, F.; Bloch, W.; Borges, U.; Burberg, T.; Collins, B.; Gunasekara, N.; Hosang, T. J.; Jacobsen, T.; Laborde, S.; Löw, A.; Schenk, A.; Schlagheck, Marit Lea; et al. (European Journal of Applied Physiology)
Abstract Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

Sportizumab – Multimodal progressive exercise over 10 weeks decreases Th17 frequency and CD49d expression on CD8+ T cells in relapsing-remitting multiple sclerosis: A randomized controlled trial - Proschinger, Sebastian; Belen, Sergen; Adammek, Frederike; Schlagheck, Marit Lea; Rademacher, Annette; Schenk, Alexander; Warnke, Clemens; Bloch, Wilhelm; Zimmer, Philipp (Brain, Behavior, and Immunity)

Predictors of six-month change in health-related quality of life in people with multiple sclerosis: A secondary data analysis of a randomized controlled trial - Patt, Nadine; Kupjetz, Marie; Schlagheck, Marit Lea; Hersche, Ruth; Joisten, Niklas; Kool, Jan; Gonzenbach, Roman; Nigg, Claudio R.; Zimmer, Philipp; Bansi, Jens (Multiple Sclerosis and Related Disorders)

Männer-Stereotypisierung in Deutschland und China: Konzeptuelles Blending von Männer-Stereotypen durch Beschriftungen auf Verpackungen von Körperpflegeartikeln - Dübbert, Alexander; Zhang, Bin (Interkulturelles Forum der deutsch-chinesischen Kommunikation)
Seit ungefähr der Jahrtausendwende konsumieren auch Männer in westlichen Ländern wie Deutschland sowie in einigen asiatischen Ländern wie China zunehmend Körperpflegeartikel, nachdem Schönheitspflege und Maskulinität sich zuvor traditionell zu widersprechen schienen. Die Verpackungen von Männerkörperpflegeartikeln enthalten in der Regel Beschriftungen einerseits zur expliziten Kennzeichnung (for men, 男性专用 [speziell für Männer] o. Ä.) und andererseits zur Werbung (ABSOLUTE MAN, 3/4/5 IN 1, STARTKLAR, 有型 [cool und stylish], 均衡 [ausbalanciert] etc.). Mit derartigen Beschriftungen, die über die Artikelverpackungen massenhaft verbreitet werden, können Unternehmen die geteilte Vorstellung von Männern als soziale Kategorie bzw. Erwartungen an diese mitkonstituieren. Das bedeutet, durch Beschriftungen auf Verpackungen von Körperpflegeartikeln können Männern stereotypische Eigenschaften zugeschrieben werden. Dieser Beitrag arbeitet heraus, wie Männer durch Beschriftungen auf Körperpflegeartikeln in Deutschland und China tendenziell stereotypisiert werden. Dazu wird die Theorie des konzeptuellen Blendings (Fauconnier und Turner 2002) für eine qualitative Auswertung eines Korpus aus Fotos von Männerkörperpflegeartikeln operationalisiert: Es werden Tendenzen ermittelt, mit welchen konzeptuellen Aspekten aus welchen Input Spaces, auf die die Beschriftungen im untersuchten Korpus verweisen, die soziale Kategorie ‚Mann‘ zu emergierenden Blends verschmolzen wird.
Keywords: Stereotyp; Konzeptuelles Blending; Verpackungsbeschriftungen; Sprachvergleich deutsch-chinesisch

Entwicklung und Validierung eines videobasierten Testinstruments zur Erfassung des Noticing mit dem Fokus auf individuelle Förderung im inklusiven Sportunterricht - Langer, Wiebke; Bruns, Julia; Erhorn, Jan (Journal for Educational Research Online)
Noticing besitzt eine hohe Bedeutung für das professionelle Handeln von Sportlehrkräften, insbesondere für den inklusiven Sportunterricht. Um eine angemessene Berücksichtigung individueller Lernvoraussetzungen und -prozesse bei der Planung und Durchführung von Unterricht zu gewährleisten, müssen die Sportlehrkräfte ihre Aufmerksamkeit gezielt auf die für die individuelle Förderung der Schüler*innen relevanten Ereignisse im zum Teil unübersichtlichen interaktiven Geschehens in der Sporthalle richten und diese auf theoretischer Grundlage interpretieren. Noticing, welches die selektive Aufmerksamkeitslenkung und das theoriegeleitete Deuten umfasst, bildet somit eine wichtige Voraussetzung, um allen Schüler*innen eine individuelle Förderung im inklusiven Sportunterricht zu ermöglichen. Die Fähigkeiten angehender Sportlehrkräften im Bereich Noticing insbesondere in inklusiven Settings sind bislang kaum untersucht worden. Diese Forschungslücke kann u.a. auf fehlende Forschungsinstrumente zur standardisierten Erfassung dieses Konstrukts zurückgeführt werden. Im Rahmen des Beitrags wird daher die Entwicklung und Validierung eines standardisierten, Videovignetten-basiertes Testinstruments zur Messung des Noticing von angehenden Sportlehrkräften im Hinblick auf individuelle Förderung im inklusiven Sportunterricht vorgestellt. Im Fokus der Validierung stehen der Testinhalt, die interne Struktur des Instruments sowie Zusammenhänge mit verwandten inhaltlichen Konstrukten. Die Ergebnisse aus drei aufeinander aufbauenden Validierungsstudien geben Hinweise auf die Reliabilität und Validität der Testwertinterpretation des Instruments ViProQiS_IF im Sinne des Noticing im Hinblick auf individuelle Förderung im inklusiven Sportunterricht.

Place Value and Regrouping as Helpful Constructs to Diagnose Difficulties in Understanding the Place Value System Stellenwert und Bündelung als hilfreiche Konstrukte zur Diagnose von Schwierigkeiten beim Verständnis des Stellenwertsystems - Jensen, Solveig; Gasteiger, Hedwig; Bruns, Julia (Journal für Mathematik-Didaktik)
Abstract The understanding of place value systems, especially the base-ten place value system, is one of the most important prerequisites to develop numeracy. The understanding of place value systems can be ascribed to two concepts, which in the tradition of the German subject-matter didactics are called regrouping principle and place value principle . Our study aims at clarifying whether these two principles can be used systematically for an effective identification of the gaps in students’ understanding to give a basis for individual support. We therefore conducted a study with N = 100 third graders (8 to 10 years old). We asked the students to work on 7 tasks on translating named units into written numbers using the place value system, in which the place value principle, the regrouping principle or both principles had to be considered. We analysed the errors qualitatively regarding which principle was violated and developed a typification of solution behaviour. The identified individual difficulties by taking the perspective of the two principles can be a starting point for individual support. Our tasks are shown to be a quick and easy way to diagnose students’ individual problems in understanding the base-ten place value system.

Development and validation of a test to measure situation-specific skills with regard to providing participation in inclusive physical education - Langer, W.; Bruns, Julia; Erhorn, J. (Teacher professional vision: Empirical perspectives)

Intervention Research on Teachers’ Professional Vision: Challenges of Current Research - Bruns, Julia (Teacher professional vision: Theoretical and Methodological Advances)

In-situ computed tomography and transient dynamic analysis – failure analysis of a single-lap tensile-shear test with clinch points - Reschke, G; Köhler, D; Kupfer, R; Troschitz, J; Gude, M; Brosius, A (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Clinching is a mechanical joining technology, in which a mainly form-fit joint is created by means of local cold forming. To characterize the load-bearing behavior of such joints, they are typically analyzed destructively, for example by tensile-shear tests in combination with metallographic sections. However, both the initiation and progress of failure can only be described to a limited extent by this method. Furthermore, these tests allow only limited conclusions about clinch points under in-service loading. More purposefully, clinch points can be analyzed nondestructively by combining in-situ computed tomography (CT) and transient dynamic analysis (TDA). The TDA continuously measures the dynamic behavior of the specimen and indicates failure events like crack initiation, which then can be evaluated thoroughly by stopping the test and performing a CT scan. To qualify the TDA for this task, it is necessary to link the observed damage behavior with specific dynamic characteristics. In this work, the complementation of in-situ CT and TDA is investigated by testing a clinched single-lap tensile-shear specimen made of aluminum. The testing procedure is stepwise: at certain displacement levels, the specimen is investigated by in-situ CT and TDA. While the in-situ CT provides the location, extent, and development of the failure phenomena, the TDA uses this information to evaluate the dynamic signal and detect relevant frequency ranges, which indicate damage events. The results demonstrate, that failure initiation and progression can be analyzed efficiently by combining both measuring systems. The TDA reliably detects relevant signal changes in the monitored frequency band. By means of in-situ computed tomography, the corresponding failure phenomena can be described in detail, enhancing the understanding of the load-bearing and deformation behavior of clinch points. The concatenation of characteristic signal changes and observed failure phenomena can henceforth be transferred to analyze complex structures during operation nondestructively by TDA.